From qualitative to quantitative description of the anomalous thermoelastic behavior of V, Nb, Ta, Pd and Pt. (22nd March 2019) - Keuter, Philipp; Music, Denis; Schnabel, Volker; Stuer, Michael; Schneider, Jochen M
Abstract: To study the anomalous thermoelastic behavior of bcc V, Nb, Ta as well as fcc Pd and Pt a density functional theory (DFT) based model is used, which allows for the calculation of the elastic constant and as a function of temperature. Available experimental trends are correctly reproduced indicating that the electronic structure mechanisms enabling anomalous behavior are captured by the model. A DFT based correlative investigation between V, Nb, Ta, Pd and Pt with anomalous thermoelastic properties and Mo and Cu with ordinary behavior reveals a high density of states (DOS) at the Fermi level to be a necessary but not sufficient condition for an anomalous thermoelastic behavior. In addition, anomalous metals in contrast to ordinary metals reallocate electronic states in the vicinity of the Fermi level upon lattice distortion, causing an increase in bond strength as identified by crystal orbital Hamilton population (COHP) analysis. Hence, we have identified the combination of high DOS and electronic reallocation upon lattice distortion to be the physical origin for anomalous thermoelastic behavior in metals. The absence of an anomaly for -type distortion in V, Nb, Ta, Pd and Pt is suggested to be due to the less pronounced reallocation of states compared to -type distortion.